Comparative effects of lived experience-lecturer-guided and teacher-led classes on mental illness awareness among Japanese high school students - Shota Fujiwara; Fumie Yamazaki; Naoko Nakayama; Koshu Sugisaki (PLoS ONE, 2025)
Improving mental health literacy in adolescents is a global priority. The purpose of this study is to examine differences in students’ attitudes across five components of mental health literacy—supportability, severity, susceptibility, recoverability, and preventability—by comparing classes led by individuals with lived experience of mental illness and textbook-based classes led by teachers. This study focuses on high school students in Japan, where educational interventions in mental health literacy remain limited. This quasi-experimental study examined changes in mental health literacy among 150 Japanese high school students (aged ≥15) following two types of instruction: one for students who received lessons from individuals with lived experience of mental illness (lecturer-guided), and another by a teacher using textbook content (non-lecturer-guided). A 24-item questionnaire measuring five mental health literacy components—supportability, severity, susceptibility, recoverability, and preventability—was administered at three time points: pre-, post-, and 3-month follow-up. Valid responses from 117 students were analyzed using factor analysis and ANOVA. Five factors were extracted with acceptable internal consistency. The lecturer-guided group showed significant post-intervention improvements in severity, susceptibility, and recoverability (p < .001), with partial retention at follow-up. The non-lecturer-guided group also showed modest gains, particularly in susceptibility. However, no significant changes were observed in supportability or preventability in either group. Lessons led by individuals with lived experience of mental illness can improve student understanding of key aspects of mental health literacy, particularly the seriousness, personal relevance, and treatability of mental illness. However, support and prevention-related beliefs may require more comprehensive or repeated interventions. These findings support the integration of lived-experience lectures into mental health education and provide a multidimensional framework for evaluating educational outcomes.